PERCEIVED STRESS, EMOTIONAL INTELLIGENCE, COPING STRATEGIES, AND MARITAL ADJUSTMENT IN DUAL EARNER COUPLES - Siddiqa, Ayesha; Majeed, Sana (Pakistan Journal of Physiology, 2021)
Background: It has often been experiential that dual earner couples with the passage of time become more frustrated and strict due to lots of burden and that may affect their marital life too. The Present study aimed to investigate the relationship among Perceived Stress, Emotional Intelligence, Coping Strategies and Marital Adjustment in Dual Earner Couples. Method: This was a cross sectional study conducted on the sample of 75 dual earner couples (n=150) with the age range of 25–45 was selected by using the Non-Probability Purposive Technique. Data was taken from different Govt. and Private Institutes of Lahore. Perceived Stress Scale (PSS), Schutte Self Report Emotional Intelligence Test (SSEIT), Brief COPE Inventory (BCOPEI) and Revised Dyadic Adjustment Scale (RDAS) were applied on the participants along with demographic questionnaire. Pearson Product Moment Correlation Coefficient, Multiple Regression analysis and Independent Sample t-test was used in the study. Results: The Results showed that there was a significant negative correlation between Perceived Stress and marital adjustment (r= -0.25, p=0.001), whereas, Emotional Intelligence (r=0.46, p=0.000) and Coping Strategies (r=0.15, p=0.033) have significant positive relationship with Marital Adjustment. Perceived Stress (p=0.23) and Coping Strategies (p=0.92) are not well predictors; however Emotional Intelligence (p=0.000) was found a significant predictor of Marital Adjustment (R2=0.22). The findings also depicted that there was no gender difference regarding the study variables. Conclusion: Perceived stress has negative but emotional intelligence and coping strategies have positive effect on marital adjustment. Pak J Physiol 2021;17(4):67–71